Biogeomorphological feedback in karst areas - Bárány-Kevei, Ilona; Kiss, Márton (Acta Geographica Debrecina Landscape & Environment series, 2016)
In the last decades, the research on ecosystem services have emerged in the field of geography. The negative impacts of human activities on the vulnerable karst areas are getting enforced quickly, which have an unfavourable influence on ecosystem service provision. On karstic areas, there are significant geographical processes, connected to biological activities. This issue is not adequately discussed in the current literature of karst ecology. In our study, we give an overview on the biogeomorphological feedbacks that change the functions and overall value of karst ecosystems.